Harmonization of Tri Hita Karana: A Sustainable Tourism Branding Strategy (Grand Istana Rama Study) - I Gede Novara Krishna; Ragil Noviyanti; Shigit Januar (Universitas Negeri Yogyakarta, 2025)
This study aims to evaluate the marketing communication strategy of Grand Istana Rama Hotel (GIR) in Kuta, Bali, and to address the research gap regarding local wisdom as a core strategic asset rather than mere ornamentation in sustainable tourism. Employing a qualitative single case study method and in-depth interviews with key management, this research analyzes how GIR radically integrates the Tri Hita Karana (THK) philosophy into its brand equity through the strategic transformation of cultural capital. The process involves examining three strategic pillars: Palemahan (environment), transformed into a 1.7-hectare